2011
DOI: 10.1080/13691058.2011.607243
|View full text |Cite
|
Sign up to set email alerts
|

The Drayang Girls of Thimphu: sexual network formation, transactional sex and emerging modernities in Bhutan

Abstract: Bhutan's sustained low HIV prevalence can be attributed to its political commitment to maintain isolation from foreign cultural influence. Recently, rising HIV prevalence has coincided with the increase in human traffic along Bhutan's borders. The majority of infections, occurring primarily through sexual contact, have appeared in the urban environments that are situated along the main transport routes. This qualitative study explored the sexual networks that form at entertainment venues in the capital city of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 9 publications
6
14
0
Order By: Relevance
“…In terms of socio-demographic characteristics, the divorced and unmarried women are engaged more in transactional sex as compared to married women. The result is consistent with the findings from the qualitative study by R. Lorway(2011) where the majority of those who engaged in transactional sex was from the divorced and unmarried categories of respondents. (4) We do not know the specific reason for their engagement in transactional sex but we speculate that it may be due to their financial hardship as a single bread earner.In general, the global studies in different settings also showed that the divorced and unmarried women are more likely to face social challenges related to poverty, income and gender inequality thus exposing them to various risk including HIV and STIs.…”
Section: Underlying Determinantssupporting
confidence: 89%
See 4 more Smart Citations
“…In terms of socio-demographic characteristics, the divorced and unmarried women are engaged more in transactional sex as compared to married women. The result is consistent with the findings from the qualitative study by R. Lorway(2011) where the majority of those who engaged in transactional sex was from the divorced and unmarried categories of respondents. (4) We do not know the specific reason for their engagement in transactional sex but we speculate that it may be due to their financial hardship as a single bread earner.In general, the global studies in different settings also showed that the divorced and unmarried women are more likely to face social challenges related to poverty, income and gender inequality thus exposing them to various risk including HIV and STIs.…”
Section: Underlying Determinantssupporting
confidence: 89%
“…The result is consistent with the findings from the qualitative study by R. Lorway(2011) where the majority of those who engaged in transactional sex was from the divorced and unmarried categories of respondents. (4) We do not know the specific reason for their engagement in transactional sex but we speculate that it may be due to their financial hardship as a single bread earner.In general, the global studies in different settings also showed that the divorced and unmarried women are more likely to face social challenges related to poverty, income and gender inequality thus exposing them to various risk including HIV and STIs. (20,(25)(26)(27) However, we cannot generalize these findings for other divorced women in Bhutan who are not working in Drayangs with same sexual behaviour as the study was confined to women who were working in the Drayang, and from them a small subset was divorced.…”
Section: Underlying Determinantssupporting
confidence: 89%
See 3 more Smart Citations